A high-density ERP study reveals latency, amplitude, and topographical differences in multiple sclerosis patients versus controls. - REILLY, RICHARD; KIISKI, HANNI; NOLAN, HUGH; WHELAN, ROBERT (My University, 2010)
Objective. To quantify latency, amplitude and topographical differences in event-related potential (ERP) components between multiple sclerosis (MS) patients and controls and to compare ERP findings with results from the paced auditory serial addition test (PASAT). Methods. Fifty-four subjects (17 relapsing remitting (RRMS) patients, 16 secondary progressive (SPMS) patients, and 21 controls) completed visual and auditory oddball tasks while data were recorded from 134 EEG channels. Latency and amplitude differences, calculated using composite mean amplitude measures, were tested using an ANOVA. Topographical differences were tested using statistical parametric mapping (SPM). Results. In the visual modality, P2, P3 amplitudes and N2 latency were significantly different across groups. In the auditory modality, P2, N2, and P3 latencies and N1 amplitude were significantly different across groups. There were no significant differences between RRMS and SPMS patients on any ERP component. There were topographical differences between MS patients and controls for both early and late components for the visual modality, but only in the early components for the auditory modality. PASAT score correlated significantly with auditory P3 latency for MS patients. Conclusions. There were significant ERP differences between MS patients and controls. Significance. The present study indicated that both early sensory and later cognitive ERP components are impaired in MS patients relative to controls.
PUBLISHED
Keywords: Neuroscience; Multiple sclerosis; Neuroscience; Next Generation Medical Devices